Pengaruh Audit Eksternal terhadap Pelaksanaan Laporan Koperasi Unit Desa - Afrijal, Afrijal (Jurnal Daya Saing, 2016)
Abstract: KUD report provides an overview of the quality rather than the board KUD, the admissibility of this report is crucial penguru management in the future. This condition is the part that needs to be observed, because the reporting is done the board is still not optimal. Through a survey conducted to 93 members KUD in Kampar provide prove that the role of external auditors in reporting KUD to members of the cooperative itself. Pengaruhn positive and significant impact on the quality of reporting is leading the auditor to audit the implementation neutrality Keywords: External Audit, Reporting KUD